A novel iron oxychloride nanosheets-based multifunctional nanocomposites for synergistic cancer treatment. (March 2022) - Yan, Xiang; Yang, Jie; Wu, Juan; Su, Han; Sun, Guowen; Ni, Yanhong; Sun, Weibin
Abstract: Glucose oxidase (GOx) has been employed as a noninvasive critical agent for cancer therapy, which mediates the generation of hydrogen peroxide (H2 O2 ) in physiological metabolism progress ·H2 O2 showed a huge benefit in enhancing synergistic cancer therapy, such as the combination of chemodynamic therapy (CDT) and starving-like therapy. Moreover, the photothermal therapy (PTT) approach induced by laser irradiation with growing attention, can be a highly effective method in minimally invasive cancer therapy. In this work, we constructed iron oxychloride nanosheet-based nanocomposites (FeOCl@AMP@GOx@PEI@PGA@Au NCs) with multiple functions, such as mediating synergistic starving-like therapy, CDT, and PTT. The functional pathways can be concluded as follows: (1) GOx participates and fosters intratumoral glycometabolism process to enhance energy consumption, and produces toxic product H2 O2 ; (2) catalase-like activity of FeOCl foster H2 O2 further decompose into oxygen (O2 ) and reactive oxygen species (ROS), which can enhance the efficacy of cancer starving-like therapy and CDT; (3) adenosine 5′-monophosphate (AMP) as part of horseradish peroxidase (HRP) can improve the activity of FeOCl NSs in producing activated H2 O2 ; (4) poly (γ-glutamic acid) (γ-PGA) as a targeted polymer can enhance tumor accumulation; (5) the loading of gold nanoparticles (AuNPs) on the surface of NCs induce the photothermal effect. Taken together, we concluded that iron-based nanomaterial FeOCl@AMP@GOx@PEI@PGA@Au NCs could excite novel aspects in nanotheranostics applications for tumor therapy.